Benign Hepatic Tumor - Balboa, Oscar; Voelker, Ricardo; Falconi, Luis (Cirugía del Uruguay, 1980)
A case of benign hepatic tumor identified as a nodular hyperplasia is reported. An analysis of this pathology is done and its possible connection with oral contraceptives and estrogens in general is pointed out.